Iklim Komunikasi Organisasi di Kantor Urusan Agama Kecamatan Hiliran Gumanti Kabupaten Solok - Feri Ilham Dani; Ali Nupiah; Refika Mastanora (IAIN Batusangkar, 2022)
This study aims to determine the organizational communication climate in the office of religious affairs (KUA) Hiliran Gumanti District, Solok Regency. The type of research that the author does is descriptive research, where the research method describes the characteristics of the phenomenon being studied. Data processing was carried out in a qualitative descriptive manner. Based on the results of the research that the author examined, the Organizational Communication Climate in the Office of Religious Affairs (KUA) of Hiliran Gumanti District by using the theory of Organizational Climate Dimensions in which the Communication Climate of the KUA of Hiliran Gumanti District includes trust, openness and candor, and upward communication flow, and internal dimensions. the formation of an organizational climate includes responsibility, quality standards of work, rewards or rewards, brotherhood and team spirit at work. While the factors that affect the organizational climate in KUA Hiliran Gumanti sub-district include leadership style, employee cultural behavior, and external factors that support work.